A novel biosensor for early diagnosis of liver cancer cases using smart nano‐magnetic metal–organic framework. (21st October 2019) - Sheta, Sheta M.; El‐Sheikh, Said M.; Abd‐Elzaher, Mohkles M.; Salem, Salem R.; Moussa, Hanan A.; Mohamed, Reda M.; Mkhalid, Ibraheem A.
Abstract: For the first time, alpha‐fetoprotein (AFP) quantification as an early test for liver cancer diagnosis competing with other interfering analytes and factors based on a novel nano‐magnetic metal–organic framework (MOF) was investigated. The novel nano‐magnetic MOF was synthesized via a simple preparation method, and characterized using various techniques. The X‐ray photoelectron spectrum of the nano‐magnetic MOF shows Cu 2p, O 1s, N 1s and C 1s peaks that evidence the presence of these elements in the sample without any impurities. Scanning and transmission electron microscopy images show the nano‐magnetic MOF with average size between 22 and 43 nm. The results of a photoluminescence study show that the nano‐magnetic MOF exhibits strong emission at 418 nm after excitation at 354 nm. Moreover, a Stern–Völmer graph shows a linear calibration curve over an AFP concentration range 1.0–520 ng ml −1 with a correlation coefficient of 0.997, detection limit of 1.18 ng ml −1 and quantitation limit of 3.58 ng ml −1 . According to the marked quenching of the photoluminescence intensity of the nano‐magnetic MOF using various concentrations of AFP, it was successfully used as a biosensor for AFP in serum samples collected from hepatitis patients in addition to healthy males and females. The quenching mechanism was well studied, and found to be a dynamic type. The present work offers a simple, low‐cost, room‐temperature and rapid technique, being non‐time‐consuming, highly accurate, selective and highly sensitive compared with most published methods. Abstract : A novel nano‐magnetic metal–organic framework was synthesized and fully characterized and used in a fast, direct, simple, low‐cost, sensitive, selective and promising analytical approach for early diagnosis of cases of hepatocellular carcinoma by determination of alpha‐fetoprotein in serum.